First practical synthesis of 2- or 3-fluoroalkylated indenols via cobalt-catalyzed [2 + 3] carbocyclization of fluorine-containing alkynes and 2-iodoaryl ketones. Issue 27 (5th July 2019) - Kumon, Tatsuya; Yoshida, Kazuhiro; Yamada, Shigeyuki; Agou, Tomohiro; Kubota, Toshio; Konno, Tsutomu
Abstract: [2 + 3] Cycloaddition reaction of fluorine-containing alkynes with various 2-iodoaryl ketones in the presence of CoCl2 (dppf) catalyst proceeded very smoothly to give the corresponding 2- or 3-fluoroalkylated indenols in 57–98% yields. These regioisomers could be successfully separated and obtained in a pure form. From X-ray crystallographic and NOESY analyses, major or minor regioisomers were determined as 3- or 2-fluoroalkylated indenols, respectively. Graphical abstract: Image 1